PENERAPAN METODE TRIPLE EXPONENTIAL SMOOTHING DALAM MERAMALKAN CURAH HUJAN DI KOTA MAKASSAR - Miftahul Asrida; Wahyuni Abidin; Ermawati (JES-MAT: Jurnal Edukasi dan Sains Matematika, 2025)
Makassar City has a tropical climate with annual fluctuations in rainfall patterns, making an accurate forecasting method necessary to support planning across various sectors. This study aims to forecast the rainfall intensity in Makassar City for the period of January–December 2024 using the Triple Exponential Smoothing method. This method was selected because it is capable of modeling time series data with trend and seasonal components. The variable used in this study was monthly rainfall intensity measured in millimeters (mm). The analyzed data consisted of monthly rainfall intensity data for Makassar City from 2018 to 2023, comprising 72 observations. The analysis was conducted by comparing the additive and multiplicative models through parameter simulation of α, β, and γ within the interval of 0–1, followed by evaluating the forecasting accuracy using the Mean Absolute Percentage Error (MAPE). The results showed that the additive model provided better forecasting accuracy than the multiplicative model, with a MAPE value of 19.16%, while the multiplicative model produced a MAPE value of 21.97%. The forecasting results indicated that the highest rainfall was predicted to occur in January, whereas the lowest rainfall was predicted in July. These findings indicate that the additive model is more appropriate for forecasting rainfall in Makassar City and can serve as supporting information for water resource management planning, hydrometeorological disaster mitigation, and decision-making related to rainfall conditions.